Evaluation of Anti-tussive Potential of Acorus calamus Linn on Ammonium Hydroxide Induced Cough Reflex in Mice - Kumar, Pandey Sunil (International Journal of Pharmaceutical & Biological Archive, 2023)
Cough is a protective physiologic reflex of the respiratory system. Its function is to remove foreign object and abnormal excessive secretions from the respiratory tract. Cough also can pathologic and is a symptom of many underlying diseases. In adults in the United States, it is the fifth most common reason for visits to ambulatory care units, accounting for 30 million visits yearly. It can be due to a variety of pulmonary conditions such as asthma, chronic obstructive pulmonary disease, and lung cancer and adds to the adverse effect; those diseases have on quality of life. Cough is also a side effect of certain medications, with angiotensin converting enzyme inhibitors being the most familiar example. This study aimed to evaluate the anti-tussive potential of Acorus calamus on ammonium hydroxide-induced cough reflex in mice. The methods involved the administration of the ethanolic extract of A. calamus at a dose of 500 mg/kg to the mice, followed by induction of cough with ammonium hydroxide. The number of coughs was counted and the results were compared to the control groups. The results of the study showed that the ethanolic extract of A. calamus significantly reduced the number of coughs induced by ammonium hydroxide when compared to the control groups. This finding suggests that A. calamus has anti-tussive potential and could be a potential candidate for the development of new anti-tussive agents. In conclusion, the study highlights the potential of natural products, such as A. calamus, in the development of new anti-tussive agents. The findings also underscore the importance of developing effective therapies for the management of cough, a common symptom of various underlying diseases. Further research is necessary to confirm these findings and elucidate the mechanism of action of A. calamus in reducing cough.